Glycaemic index and glycaemic load of foods and food products in Malaysia: a review - Osman, M. H.; Mohd Yusof, Barakatun Nisak; Ismail, Amin (Universiti Putra Malaysiara, 2021)
Glycaemic index (GI) is a method used to classify the type of carbohydrate-rich foods according to their effect on postprandial glycaemic responses. While the GI concept provides a measure of carbohydrate quality, glycaemic load (GL) quantifies the overall glycaemic effects by considering both the quality and quantity of carbohydrate-rich foods. The higher the GI and GL of the foods, the greater the elevation of blood glucose and insulin demand. Reduction in dietary GI and GL are associated with the prevention and control of chronic diseases, including type 2 diabetes. Although the GI concept has been applied in various nutrition-related interventions in Malaysia, a reliable database on Malaysian foods and food products are scarce. This review attempts to determine and compile reliable data of GI and GL values of Malaysian foods and food products. A literature search was performed using predefined terms and criteria not only limited to web-based databases (n = 20), but included abstracts (n = 6) and manufacturer (n = 1). The GL value for each food was calculated. A total of 83 foods was identified with the most common being rice (25.3%) and bread (16.9%), either eaten alone or in mixed meals. Food with the highest GI value was sago (GI = 156; GL= 59), while food with the lowest GI value was spaghetti with chicken soup (GI = 35; GL = 4). This review shows that the number of foods and food products with the assigned GI and GL values in Malaysia is still limited, which warrants for more studies in this area.